Novel theranostic nanoplatform for complete mice tumor elimination via MR imaging-guided acid-enhanced photothermo-/chemo-therapy. (September 2018) - Li, Bei; Tang, Jie; Chen, Weiyu; Hao, Guanyu; Kurniawan, Nyoman; Gu, Zi; Xu, Zhi Ping
Abstract: Non-invasive imaging-guided tumor therapy requires new-generation bio-nanomaterials to sensitively respond to the unique tumor microenvironment for precise diagnosis and efficient treatment. Here, we report such a theranostic nanoplatform by engineering defect-rich multifunctional Cu-doped layered double hydroxide (Cu-LDH) nanoparticles, which integrates pH-sensitive T1 -magnetic resonance imaging (MRI), acid-enhanced photothermal therapy and heat-facilitated chemotherapy. As characterized with EXAFS and XPS, smaller Cu-LDH nanoparticles possess a considerable amount of defects around Cu cations, an advantageous microstructure that enables a high photothermal conversion of 808 nm NIR laser (53.1%). The exposure of CuOH octahedra on the LDH surface makes the photothermal conversion significantly acid-enhanced (53.1% at pH 7.0 vs. 81.9% at pH 5.0). This Cu peculiar microstructure also makes T1 -MRI very pH-sensitive, a desirable guide for subsequent tumor photothermal therapy. Combined photothermal therapy and chemotherapy lead to nearly complete elimination of tumor tissues in vivo with a low injection dose of agents. Therefore, this novel defect-rich Cu-LDH nanoplatform is one of promising tumor-specific nanotheranostic agents for non-invasive imaging-guided combinational therapy. Graphical abstract: Image 1